PENENTUAN PRIORITAS PENANGANAN KERUSAKAN JALAN DI KOTA SOLOK MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) (Studi Kasus: Jalan Datuk Perpatih Nansabatang, Jalan Sawah Sianik, Jalan Veteran, Jalan Kol. Drs. Zahlul St. Kebesaran) - Ahmad Refi; Diyo Atmatri Putra; Angelalia Roza (Ensiklopedia of Journal, 2022)
To support the acceleration of the regional or regional economy, the government has prioritized road construction projects. The better the road performance will make it easier for people to carry out their activities. Based on data from the Solok City Road Network in 2019/2020, it is known that out of a total of 221,700 km of road length in Solok City, there are 35,917 km that have been severely damaged, 20,488 km have been moderately damaged, 16,970 km are lightly damaged. The large number of road sections that have been damaged cannot be repaired at the same time, so to make a decision, a special criteria is needed in handling road damage. The objectives in this study are: determining the criteria considered in handling road damage and determining the order of priority for handling road damage in Solok City. This study was conducted to study 4 road sections using the Analytical Hierarchy Process (AHP) method. This research is descriptive quantitative, while the data sources used in this study are primary data obtained from the distribution of questionnaires to 30 respondents prepared by the paired comparison matrix method to obtain the criteria relative weight value, subcriteria weight value and consistency level value in each paired comparison matrix. The results of tabulating data from the questionnaire are processed using Microsoft Excel. Based on the results of data processing, a weight order of each criterion was obtained, namely: Road Damage (31.10%), Traffic Volume (25.00%), Economy (23.50%) and Accessibility (20.40%). Meanwhile, the road sections that are prioritized for repair are: Kol Road. Drs. Zahlul ST. kebesaran road (27.50%), Veteran Road (26.00%), DT. Perpatih Nan Sabatang road (24.00%), Sawah Sianik road (22.50%). From the results of the respondent's answer, the main criterion that needs to be considered in handling road damage is the criterion for road damage and the road that is prioritized for repair is Jalan Kol. Drs. Zahlul ST. Kebesaran, which is a road with a higher level of damage in the field, is in line with field conditions with a road damage weight of 333.85 M2 (3.42%).